Sutsidial Behavioral Danger: Concept and Forms of Display - Gazieva Nozima Shoirjonovna (Periodica Journal, 2022)
The article puts forward the basic laws, features of the manifestation of social behavior, as well as related theoretical approaches. In particular, the main psychological factors and mechanisms of the origin of suicidal behavior in the personality of the adolescent are shown. The scientific researches of foreign scientists on the problem are also presented.
Keywords: adolescent personality; sutidial behavior; behavior; risk